INTRODUKSI KONSEP BERSIH PANTAI (COASTAL CLEANUP) DI PANTAI SINDANGKERTA, KECAMATAN CIPATUJAH, KABUPATEN TASIKMALAYA - Yusuf Awaludin, Mochammad (Jurnal Harpodon Borneo, 2011)
Sindangkerta beach is a local tourism site which is located in Tasikmalaya, West Java. Marine debris is the problem for improving the tourism development in that location. International Coastal Cleanup (ICC) concept had been introduced to local people and local tourists. There was several important points obtained from this introductory activity. First, the concept was able to improve people and tourists understanding of coastal cleanness. Second, it has improved people awareness of marine debris. Third, continuity of this program and extra cleanliness tools are needed in order to develop this local tourism. Keywords : Sindangkerta Beach, coastal cleanup, marine debris.